Burndown systems with residual activity for fallow areas infested with fleabane - Oliveira Neto, Antonio Mendes; Constantin, Jamil; Silvério de Oliveira Júnior, Rubem; Guerra, Naiara; de Almeida Dan, Hugo; Marcos Silva Vilela, Lélio; Von Pinho Botelho, Lucas; André Ávila, Lucas (Federal University of Piauí, 2013)
This work aimed at evaluating the burndown efficiency of sequential applications of herbicides onConyza spp. in areas that remained in fallow during the winter, as well as at monitoring the residualeffect of herbicides in soil on weed control within soybean cycle. The experiment was carried outin a field where soybean was the previous summer crop and that remained non-cultivated duringthe winter. All herbicide treatments were composed by two burndown sequential applications: thefirst by spraying a tank mixture of glyphosate+2,4-D and the second by tank mixtures composed byglyphosate plus one or more herbicides with residual activity in the soil (chlorimuron-ethyl, flumioxazinand diclosulam). Evaluations included the burndown efficiency on emerged fleabane (plants ≥ 20cm and plants < 20 cm) and the residual effect of herbicides on the new fluxes of morningglory andsida. Soybean was sowed five days after the second burndown application. One single applicationof glyphosate+2,4-D was sufficient to control completely fleabane plants < 20 cm. For plants ≥20 cm,tank mixtures of glyphosate plus either chlorimuron-ethyl or diclosulam in the second applicationprevented the occurrence of fleabane regrowth, without however eliminate them. Treatmentscontaining herbicides with residual activity in soil (chlorimuron-ethyl, flumioxazin, chlorimuronethyl+flumioxazin and diclosulam) were in suppressing the development of morningglory and sida.